Adaptation of Diverse Maize Germplasm to Spring Season Conditions in Northeast China - Yi Li; Zhiyuan Yang; Yong Shao; Zhenguo Jin; Li Gao; Yang Yu; Fengyi Zhang; Yuxing Zhang; Yuantao Nan; Mingshun Li; Degui Zhang; Zhuanfang Hao; et al. (Agronomy)
Northeast China (NEC) is a major spring maize (Zea mays L.) growing belt, and the outputs substantially influence national grain production. However, the maize grain yield per unit area has little changes in recent years, partially due to the lack of elite germplasm resources and innovation. Therefore, this study aimed to determine the performance of diverse populations in NEC to propose appropriate strategies for the utilization of elite germplasm to broaden the genetic base of Chinese germplasm. Fifteen diverse maize populations from the International Maize and Wheat Improvement Center (CIMMYT) and the U.S. were crossed to two local tester lines, representing Chinese heterotic groups Reid and Lancaster, for evaluating the combining ability and heterosis in three locations (Gongzhuling, Jilin Province, and Harbin and Suihua, Heilongjiang Province) in NEC over two years. The U.S. (BS13(S)C7 and BS31) and Chinese (Ji Syn A) populations exhibited more favorable alleles for high yield potential in all locations tested. Furthermore, the PH6WC × BS31 and PH6WC × Ji Syn A crosses had higher grain yields, and an appropriate number of days to silking, ear height, and resistance to lodging at Gongzhuling and Harbin in NEC. The best strategies for utilizing these diverse germplasms may be to develop new inbred lines from the existing elite populations or improve the grain yield and resistance to lodging of the elite line PH4CV for broadening the genetic base of the Chinese group Lancaster in NEC.